Comparison of polycaprolactone and calcium hydroxylapatite dermal fillers in a rat model. Issue 1 (4th January 2021) - Yanatma, Irem; Sarac, Gulbahar; Gul, Mehmet; Gul, Semir; Kapicioglu, Yelda
Abstract: Polycaprolactone (PCL) and calcium hydroxylapatite (CaHA) are semipermanent dermal fillers that are frequently preferred in the last decade. This study aims to compare the effects of these two fillers in the rat skin. A total of 30 female rats were divided into; control, PCL, and CaHA group. Tissue samples taken at the second and fourth month were stained with hematoxylin‐eosin, Masson trichrome, collagen type 1, and 3 immunohistochemical antibodies. Collagen density was quantitatively compared using the Image J computer program. At 2 and 4 months, the density of collagen increased in both filler groups compared to the control group. There was no significant difference between collagen density or type 1 and type 3 collagen H scores in the filler groups. The number of fibroblast nuclei was significantly higher in the PCL group at 4 months compared to the other two groups. Dermis thickness was found to be superior in both filler groups compared to the control group at the fourth month, there was no significant difference between the filler groups. We compared the effect of CaHA and PCL filler on collagenization histologically and immunohistochemically. We found that PCL and CaHA fillers are effective in increasing dermal collagen density, type 1 and type 3 collagen amount, and preventing dermis atrophy and showed that they have no advantage over each other in this respect. We have shown that PCL filler provides more fibroblast increase compared to CaHA filler and the effect of stimulating fibroblast proliferation takes longer.